Teaching Fourier series, partial differential equations and their applications with help of computer algebra system - Perjési-Hámori, Ildikó; Sárvári, Csaba (Teaching Mathematics and Computer Science, 2009)
In this paper, some examples of Fourier series and partial difference equations will be shown to demonstrate opportunities for CAS use in various circumstances. The well-known white-box – black-box teaching-learning techniques and the modularization will be used to allow the use of the same worksheet in different ways.